Desenvolvimento de estratégias cognitivas implicadas na aprendizagem de uma língua estrangeira no contexto de oficinas de jogos - Silva, Sirley Trugilho da (2005)
The purpose of this research was to investigate whether the development of cognitive strategies implied in foreign language learning could be facilitated by the practice of games of rules during workshops. Previous research had used this instrument to develop reasoning abilities. Three students of an English as a foreign language course who were in the beginners classes participated in this research. Since they had no previous contact with the language and felt some initial problems with English, it was assumed that the changes regarding the buildup of specific learning strategies would be significant during this period. The participants teachers filled in a form with some considerations about their performance prior to and following the participation of the students in the workshops, which were held weekly, during one hour, amounting to 10 meetings, using the versions of the Mastermind game, known as: abc and hidden word , besides the memory game. During the workshops, the participants were monitored and an observation protocol was filled in; a diary was kept in which pertinent information was noted, and the matches played were registered on specific forms. In general, the participants demonstrated a reasonable level of performance in the workshops. The main questions that appeared during the meetings were related to lack of attention, shyness and lack of confidence. However, it was possible to observe the construction of new cognitive strategies many times during the meetings, which seems to have affected the performance of each participant in the classroom, as the respective teachers emphasized. The conclusion, therefore, is that the practice of games of rules can in fact help the development of cognitive strategies implied in foreign language learning in a very interesting way.